A comparative study of visual representations in conventional, digitized and interactive high school science textbooks. Issue 2 (3rd April 2017) - Chen, Xiaoning
Abstract: With emerging new technologies being applied in teaching and learning, this study compares visual representations in three different high school biology textbook formats and analyses the senses engaged in viewing and understanding the science content represented through these visuals. The findings show that while a similar pattern is observed in using various categories of visuals in the biology textbooks, several new multimedia features have emerged in digitized and interactive textbooks. These new features have an impact on how students engage the senses of vision and touch in science learning. The implications regarding the integration of effective multimedia features in designing visual representations in science textbooks and the need to support students to become confident and critical digital citizens are discussed.